Omnibus Law Discourse on Television: Support Elite or Public? - Hedi Pudjo Santosa; Nurul Hasfi; Triyono Lukmantoro; Himmatul Ulya; Yofiendi Indah Indainanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
The mass media construct discourses with major impact on the formation of public opinion. This study identifies mass media discourse of the Job Creation Law produced in the 22 television dialogue programs aired by TV One, Metro TV, Kompas TV, and CNN Indonesia. By focusing on indicators of discourses, sources, and duration of speakings this study finds the dominant discourse of positive sentiment towards the Job Creation Law – which is mainly brought by the government elite and businessmen – namely economic improvement and investment. In contrary, television program shaped negatif sentiment of the Law in narrower space – which was brought mainly by activists, academics and laborers – including the Job Creation Law disserve labours, endangers the environment and sighned in unprocerudal mecanism. The data shows that the television dialogue has provide more space for the elite than the public in discussing the controversial issue of the Job Creation Law.